A case report on Meigs’ syndrome and elevated serum CA-125: A rare case report - Khanduja, Divya; Kajal, NC (Journal of Pulmonology and Respiratory Research, 2021)
Meigs syndrome is an uncommon presentation, where a benign ovarian neoplasia presents along with ascites and pleural effusion. About 1% of ovarian neoplasia can present as Meigs syndrome. Patients with Meigs’ syndrome and elevated serum CA-125 are not frequently reported. We report a case of a 50-year-old women who presented with shortness of breath, cough, weight loss of one and half month duration. Chest radiograph of the patient with clinical examination of patient confirms pleural effusion as cause of progressive shortness of breath. The presence of a pelvic mass and elevated serum CA-125, which raised the possibility of malignancy. After complete resection of tumor, the pathologic reports confirmed a benign ovarian neoplasia. We highlight the importance of suspicion, careful general examination, radiological assessment and histological tests to confirm the diagnosis of Meigs’ syndrome.